Educational and testing and measurement : classroom application and practice - Kubiszyn, Tom; Borich, Gary (New Jersey : John Wiley & Son, Inc., 2010)
Introduces students to the dramatic developments that have occurred in the field over the last few years. Details the US national policy changes that have fostered the ongoing, dramatic and controversial changes in general education and special education testing and assessment practices.
An introduction to contemporary educational te4sting and measurement -- High-stakes testing -- Response-to-intervention (RTI) and the regular classroom teacher -- The Purpose of testing -- Norm-referenced and criterion-referenced tests and content validity evidence -- Measuring learning outcomes -- Writing objective test items -- Writing essay test items -- Performance-based assessment -- Portfolio assessment -- Administering, analyzing and improving the test or assessment -- Marks and marking systems -- Summarizing data and measures of central tendency -- Variability, the normal distribution, and converted scores -- Correlation -- Validity evidence -- Reliability -- Accuracy and error -- Standardized tests -- Types of standardized tests -- In the classroom : a summary dialogue
Includes bibliographical references and index.
Keywords: EDUCATONAL TESTS AND MEASURMENTS